PEMBERDAYAAN KELOMPOK EKONOMI PRODUKTIF MELALUI PELATIHAN PEMBUATAN PUPUK ORGANIK DARI KULIT PISANG - Hartati, Tri Mulya; Dwiputranti, Oktora (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Nusa Cendana, 2021)
ABSTRACT The existence of the Covic-19 pandemic also affects the economic factors of the community that interfere with the immune system, so there is a need for productive activities that can increase added value. Banana peel utilization technology aims to train the community in dealing with plant waste management. This community service activity was carried out in Ngade Village, South Ternate District, Ternate City Regency. The target of the service participants is a group of young people who are members of the productive economic group